High Prevalence of Hypertension in Ethiopian and Non-Ethiopian HIV-Infected Adults. (29th January 2018) - Korem, Maya; Wallach, Tali; Bursztyn, Michael; Maayan, Shlomo; Olshtain-Pops, Karen
Abstract : Objectives . Prevalence of hypertension has not been studied in the Ethiopian HIV-infected population, which represents 60% of the patients in our AIDS unit. Our aim was to identify risk factors and characterize the prevalence of hypertension in the population monitored at our unit. Methods . A retrospective chart review categorized subjects according to their blood pressure levels. Hypertension prevalence was determined and stratified according to variables perceived to contribute to elevated blood pressure. Results . The prevalence of hypertension in our study population was significantly higher compared to the general population (53% versus 20%, P < 0.0001 ) and was associated with known risk factors and not with patients' viral load and CD4 levels. Ethiopian HIV-infected adults had a prominently higher rate of blood pressure rise over time as compared to non-Ethiopians (P = 0 . 016 ). Conclusions . The high prevalence of hypertension in this cohort and the rapid increase in blood pressure in Ethiopians are alarming. We could not attribute high prevalence to HIV-related factors and we presume it is part of the metabolic syndrome. The lifelong cardiovascular risk associated with HIV infection mandates hypertension screening and close monitoring in this population.